2020
DOI: 10.1371/journal.pone.0231004
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer diagnosis by analysis of serum N-glycans using MALDI-TOF mass spectroscopy

Abstract: Blood and serum N-glycans can be used as markers for cancer diagnosis, as alterations in protein glycosylation are associated with cancer pathogenesis and progression. We aimed to develop a platform for breast cancer (BrC) diagnosis based on serum N-glycan profiles using MALDI-TOF mass spectroscopy. Serum N-glycans from BrC patients and healthy volunteers were evaluated using NosQuest's software "NosIDsys." BrC-associated "NosID" N-glycan biomarkers were selected based on abundance and NosIDsys analysis, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…This is a challenge encountered also in other fields, such as metabolomics and proteomics [148] , [149] , [150] , and is partly caused by the shortage of large and well-defined prospective clinical cohorts (or their limited accessibility) and an insufficient statistical evaluation of the initial findings, resulting in poor validation of initial results. An example would be the reporting of 8 differentially expressed N -glycans in 82 breast cancer patients compared to 27 healthy controls in one study [151] , while a different study reported 25 different N -glycans to be differentially expressed in 256 breast cancer patients compared to 311 healthy controls [152] . While the analytical methods used were different, it is highly likely that these incongruent results are confounded by general descriptors of the population, such as age, sex and BMI [14] , [38] , [153] .…”
Section: Other Considerations For the Development Of High-quality Clinical Glycomics Tests For The Medical Laboratorymentioning
confidence: 99%
“…This is a challenge encountered also in other fields, such as metabolomics and proteomics [148] , [149] , [150] , and is partly caused by the shortage of large and well-defined prospective clinical cohorts (or their limited accessibility) and an insufficient statistical evaluation of the initial findings, resulting in poor validation of initial results. An example would be the reporting of 8 differentially expressed N -glycans in 82 breast cancer patients compared to 27 healthy controls in one study [151] , while a different study reported 25 different N -glycans to be differentially expressed in 256 breast cancer patients compared to 311 healthy controls [152] . While the analytical methods used were different, it is highly likely that these incongruent results are confounded by general descriptors of the population, such as age, sex and BMI [14] , [38] , [153] .…”
Section: Other Considerations For the Development Of High-quality Clinical Glycomics Tests For The Medical Laboratorymentioning
confidence: 99%
“…solid phase extraction (SPE), was performed based on previously described methods 14 . Serum N-glycans were www.nature.com/scientificreports/ released by an enzymatic reaction using PNGase F, followed by a purification step using columns packed with porous graphite carbon (PGC).…”
Section: N-glycan Preparation N-glycan Preparation Including Enzymamentioning
confidence: 99%
“…Analytical methods. Sample and matrix preparation for MALDI-TOF MS analysis was conducted as described previously 14 . For preparing the matrix solution, 2,5-dihydroxybenzoic acid (DHB) was dissolved in a mixture of 40 mM sodium chloride solution and ACN (3:1, v/v) to a final concentration of 20 mg/mL.…”
Section: N-glycan Preparation N-glycan Preparation Including Enzymamentioning
confidence: 99%
See 2 more Smart Citations